BENTUK ALIH KODE DAN FAKTOR DALAM TRANSAKSI JUAL BELI PADA MASYARAKAT MULTIETNIS DI PASAR SAKOK SINGKAWANG - Mayori, Dhita Elsa; Zulfahita; Wirawan, Gunta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study ai This study aims to describe Code Switching and Code Mixing of Multiethnic Community Language in Sakok Market, Singkawang. The method used in this study is a descriptive method. The form of this research is a qualitative form. The data sources in this study are the speech of sellers and buyers and the data in this study is code switching. Data collection techniques used in this study are tapping techniques, recording techniques and note-taking techniques. Data analysis techniques are carried out by collecting data, transcribing data, classifying data and then analyzing data. Based on data analysis and discussion, it can be concluded that the form of code switching of multiethnic communities in Sakok Market, Singkawang is 17 data and the factors causing code switching of multiethnic communities in Sakok Market, Singkawang is 4 data. This research can be implemented in class IX with this being applied as teaching materials for learning Indonesian in descriptive texts of the Merdeka curriculum based on learning outcomes (CP) phase D, specifically CP elements of speaking, writing and listening.